2016
DOI: 10.1111/bph.13583
|View full text |Cite
|
Sign up to set email alerts
|

The novel H2S donor 4‐carboxy‐phenyl isothiocyanate inhibits mast cell degranulation and renin release by decreasing intracellular calcium

Abstract: BACKGROUND AND PURPOSEHydrogen sulfide (H 2 S) modulates many pathophysiological processes, including inflammation and allergic reactions, in which mast cells act as major effector cells. IgE receptor (FcεRI) cross linking leads to an increase in intracellular calcium ([Ca +2 ] i ), a critical step in mast cell degranulation. The aim of this study was to investigate the role of H 2 S in [Ca +2 ] i -dependent mast cell activation. EXPERIMENTAL APPROACHWe investigated the effects of H 2 S, either endogenously p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Many studies demonstrated that H 2 S behaves as a vasculoprotective gasotransmitter by modulating different cellular pathways and interfering with a variety of vascular diseases. Indeed, H 2 S inhibits atherogenic modification of low-density lipoproteins (LDL) [11] , prevents monocytes adhesion due to ECs activation [12] , clearly promotes vasorelaxing responses [13] , decreases intimal hyperplasia by inhibiting vascular smooth muscle cells (VSMC) migration and proliferation [14] , limits vascular calcification [15] , thrombogenesis and platelet aggregation [16] , inhibits macrophage foam cell formation and degranulation [17] , limits inflammatory responses and reduces plasma homocysteine (Hcy) levels in experimental animals [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies demonstrated that H 2 S behaves as a vasculoprotective gasotransmitter by modulating different cellular pathways and interfering with a variety of vascular diseases. Indeed, H 2 S inhibits atherogenic modification of low-density lipoproteins (LDL) [11] , prevents monocytes adhesion due to ECs activation [12] , clearly promotes vasorelaxing responses [13] , decreases intimal hyperplasia by inhibiting vascular smooth muscle cells (VSMC) migration and proliferation [14] , limits vascular calcification [15] , thrombogenesis and platelet aggregation [16] , inhibits macrophage foam cell formation and degranulation [17] , limits inflammatory responses and reduces plasma homocysteine (Hcy) levels in experimental animals [18] .…”
Section: Introductionmentioning
confidence: 99%
“…CSE is the main enzyme for H 2 S production in the cardiovascular system (Wang, ; Wallace and Wang, ). Previous research found that H 2 S has the potential to produce vasoconstriction or vasodilatation, angiogenesis, smooth muscle growth or apoptosis, cardioprotection and other effects (Mani et al, ; Tsikas and Cooper, ; Ping et al, ; Dunn et al, ; Katsouda et al, ; Marino et al, ). Our studies have suggested that H 2 S attenuates myocardial hypertrophy and fibrosis in spontaneously hypertensive rats (SHR) (Meng et al, ,c; Meng et al, ), inhibits atherosclerotic plaque formation and inflammation in the aorta of apolipoprotein E −/− mice fed a high fat diet (Liu et al, ), suppresses oxidative stress and apoptosis in myocardial ischaemia and reperfusion injury (Meng et al, ), augments mitochondrial function and the anti‐oxidative capacity of endothelial cells (Xie et al, ), and activates nuclear factor E2‐related factor 2 (Nrf2) to alleviate diabetes‐accelerated atherosclerosis both in vitro and in vivo (Xie et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained using the natural isothiocyanate sulforaphane (present in several plants of Brassicaceae family) indicate that the antiviral effect of Brassicaceae extracts can be mainly attributed to their isothiocyanate metabolites. As reported above, isothiocyanates have been recently described as smart H 2 S donors by Calderone and colleagues (Calderone et al, 2016;Citi et al, 2014Citi et al, , 2019Lucarini et al, 2018;Marino et al, 2016;Martelli, Piragine, et al, 2020;Martelli et al, 2014;Testai et al, 2016). In particular, sulforaphane demonstrated antiviral activity against the influenza A/WSN/33 H1N1virus by reducing virus replication in vitro using canine kidney cells at low micromolar concentrations (Zhansheng et al, 2019).…”
Section: H 2 S and Viral Infectionsmentioning
confidence: 90%